2018
DOI: 10.1039/c7ob02858j
|View full text |Cite
|
Sign up to set email alerts
|

A mild method for synthesizing carboxylic acids by oxidation of aldoximes using hypervalent iodine reagents

Abstract: A mild oxidation method for the conversion of aldoximes to carboxylic acids was developed mediated by hypervalent iodine reagents. This method covers a wide range of functionalized aldoximes and proceeds under mild conditions, utilizing PhI(OH)OTs as an oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The reaction proceeded via hydroxamic acid generated by the oxidation of aldoxime; further oxidation afforded a nitroso compound, which underwent hydrolysis furnishing as the carboxylic acid (Scheme 1). 5 By contrast, we found that the reaction of a ketoxime with a hypervalent iodine reagent showed different reactivity. The combination of PhI(OAc)2 and a Lewis acid promoted Beckmann rearrangement under mild reaction conditions.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The reaction proceeded via hydroxamic acid generated by the oxidation of aldoxime; further oxidation afforded a nitroso compound, which underwent hydrolysis furnishing as the carboxylic acid (Scheme 1). 5 By contrast, we found that the reaction of a ketoxime with a hypervalent iodine reagent showed different reactivity. The combination of PhI(OAc)2 and a Lewis acid promoted Beckmann rearrangement under mild reaction conditions.…”
mentioning
confidence: 77%
“…2 A Lewis acid is typically used for Beckmann rearrangement for activation of the oxime, along with heating. 3 We have studied the reaction of oximes with hypervalent iodine reagents 4 and observed an interesting transformation that depends on the type of oxime: aldoxime 5 or ketoxime. 6 The reaction of aldoximes with Koser's reagent [PhI(OH)OTs] in dimethyl sulfoxide-water afforded the corresponding carboxylic ac-ids in good to high yields.…”
Section: O Efficient and Reliable Transformation To Ketonementioning
confidence: 99%
“…We have investigated hypervalent iodine-mediated reactions, such as the construction of heterocycles using oxidative rearrangement, 9 the oxidation of aldoxime to carboxylic acid, 10 Beckmann rearrangement, 11 and decarboxylative halogenation. 12 We first attempted deprotection using PhI(OAc) 2 as a hypervalent iodine reagent in (CH 2 Cl) 2 at room temperature, but the reaction did not proceed (Table 1, Entry 1).…”
mentioning
confidence: 99%
“…The 1,3-dipolar cycloaddition of nitrile oxides with various alkenes and alkynes is a powerful C–C/C–O bond-forming transformation to deliver five-membered heterocycles, isoxazolines or isoxazoles, which are versatile precursors for β-hydroxy carbonyls and γ-amino alcohols in the chemical synthesis of (non)­natural products. Generation of the nitrile oxides is critical to this [3 + 2]-cycloaddition and often achieved by one of two strategies: dehydration of nitroalkanes or oxidation of aldoximes , (Scheme a). The oxidative process has received much attention toward methodology development and more applications in total synthesis of complex molecules presumably because of the readily available aldoximes (condensation of aldehyde and hydroxylamine), mild and selective oxidation conditions, and tolerance of various functional groups.…”
mentioning
confidence: 99%